1996
DOI: 10.4315/0362-028x-59.12.1260
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Pepperoni Processes for Control of Escherichia coli O157:H7

Abstract: The outbreak of Escherichia coli O157:H7 linked with dry-cured salami in late 1994 prompted regulatory action that required manufacturers of fermented products to demonstrate a 5-log unit reduction in counts of this pathogen during processing. Therefore, pepperoni batter (75% pork:25% beef with a fat content of ca. 32%) was inoculated with a pediococcal starter culture and a five-strain mixture of E. coli O157:H7 (≥2 × 107 CFU/g) and stuffed into 55-mm diameter fibrous casings 47 cm in length. The viability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 0 publications
3
62
1
Order By: Relevance
“…The data obtained in this study has, perhaps, greater utility than that from other studies (3,8,10), as it can be used by a manufacturer to identify an optimum heat treatment step which meets relevant product requirements, in terms of product safety, while maintaining other important sensory characteristics.…”
Section: Vol 66 2000mentioning
confidence: 89%
See 2 more Smart Citations
“…The data obtained in this study has, perhaps, greater utility than that from other studies (3,8,10), as it can be used by a manufacturer to identify an optimum heat treatment step which meets relevant product requirements, in terms of product safety, while maintaining other important sensory characteristics.…”
Section: Vol 66 2000mentioning
confidence: 89%
“…Other heating protocols have also been designed for this purpose (3,8,10). The heat treatments reported by these researchers as effective in these products are milder than the treatments identified as necessary in this study.…”
Section: Vol 66 2000mentioning
confidence: 97%
See 1 more Smart Citation
“…The ability of E. coli O157:H7 to adapt to acid environments (11) has caused this microorganism to be regarded as one of the most dangerous pathogens in fermented meat products. Several studies have shown that E. coli O157:H7 is able to survive the processes of fermentation, drying, and storage when this microorganism is present at high numbers (14,16,27). The use of different starter cultures during fermentation has been unsuccessful in achieving the required 5-log 10 -unit reduction of E. coli O157:H7 (12,22).…”
mentioning
confidence: 99%
“…The use of different starter cultures during fermentation has been unsuccessful in achieving the required 5-log 10 -unit reduction of E. coli O157:H7 (12,22). Heat treatments seem to be the best way to reduce the numbers of this pathogen in semidry sausages; however, physical characteristics of dry sausage change during heating, and the products no longer resemble uncooked fermented sausages (16).…”
mentioning
confidence: 99%